BLOCKCHAIN-BASED ACADEMIC RECORDS FOR HYBRID EDUCATION: SECURING DIGITAL CREDENTIALS IN GLOBAL CRISIS CONTEXTS - Jelena Dordevic; Luka Stojanovi; Tamara Markovi (Journal Neosantara Hybrid Learning, 2025)
The COVID-19 pandemic and other global crises have exposed the fragility of traditional academic record-keeping systems, particularly in hybrid and remote education contexts. Paper-based credentials are vulnerable to disruption, loss, and forgery, while centralized digital systems often lack interoperability, transparency, and long-term security. This study investigates the application of blockchain technology for managing academic records in hybrid education settings, with a focus on ensuring secure, tamper-proof, and universally verifiable digital credentials. The research adopts a qualitative-quantitative mixed-methods approach, combining technical prototype testing with stakeholder interviews involving educators, IT administrators, and students across five countries. The blockchain-based system was evaluated based on criteria including data integrity, accessibility, user autonomy, and system scalability. Results indicate that the blockchain model ensured high data security, reduced administrative overhead, and enabled cross-border credential verification without reliance on third-party intermediaries. Participants reported increased trust in the permanence and authenticity of academic records. The study concludes that blockchain offers a resilient infrastructure for academic credentialing, particularly in times of crisis when decentralized, transparent, and immutable systems are critical for ensuring educational continuity and global mobility.